Metal Nitride Catalysts for Photoelectrochemical and Electrochemical Catalysis - Hee Ryeong Kwon; Jin Wook Yang; Ho Won Jang (Exploration)
ABSTRACT Metal nitrides have emerged as promising materials for photoelectrochemical and electrochemical catalysis due to their unique electronic properties and structural versatility, offering high electrical conductivity and abundant active sites for catalytic reactions. Herein, we comprehensively explore the characteristics, synthesis, and application of diverse metal nitride catalysts. Fundamental features and catalytic advantages of metal nitrides are presented in terms of electronic structure and surface chemistry. We deal with synthetic principles and parameters of metal nitride catalysts in terms of nitrogen source, introducing synthesis strategies of metal nitrides with various morphologies and phases. Recent progress of metal nitride catalysts in (photo)electrochemical reactions, such as hydrogen evolution, oxygen evolution, oxygen reduction, nitrogen reduction, carbon dioxide reduction, and biomass valorization reactions, is discussed with their tailored roles. By providing future direction for remaining challenges, this review aims to guide the design of metal nitride catalysts from a materials point of view, contributing to expanding into energy and environmental technologies.